Disharmoni Keluarga Akibat Judi Online di Kabupaten Sidoarjo Perspektif Teori Sistem Keluarga Al-Qur’an: Family Disharmony due to Online Gambling in Sidoarjo District Perspective of Qur’anic Family System Theory - Ratna Suraiya; Sitti Atiyatul Mahfudoh; Nashrun Jauhari; Mohamad Salik (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
This research aims to reveal the forms of family disharmony that occur due to online gambling in Sidoarjo district, and to formulate strategic steps to resolve disharmony problems in order to achieve the goals of Islamic family law. Research analysis uses Zainab al-'Alwani's Al-Quran Family Systems Theory which is based on the basic concept of maqāṣid al-Qur'ān values ​​in the field of Islamic family law, with the characteristics of universalistic (Kulliyyah), contextual thinking. (wāqi'iyah) and tendential (ta'ṣīliyah). This theory defines the family as not limited to the nuclear family consisting of father, mother and children, as per the western perspective, but also to marital relations, family and kinship relations. This field research method uses a qualitative approach with analytical descriptive data. Research results: (1) Family disharmony due to online gambling in Sidoarjo district occurs in three categories, namely the mild category in the form of husband and wife conflict, the moderate category in the form of husband and wife conflict involving relatives, and the serious category with a divorce suit before the religious court; (2) The strategy for overcoming family disharmony is to implement the universal values ​​of maqāṣid al-Qur'ān in the field of family law in family life. For the mild category of disharmony by implementing the value of monotheism (maqṣud al-Tawḥīd) through strengthening the spirituality of husband and wife, and by implementing the value of couplehood (maqṣud al-Zawjiyyah) through strengthening marital commitment and gender partnership. For disharmony in the moderate category, implementation of the value of maintenance (maqṣud al-Wilāyah) through care and harmony between relatives. Meanwhile, for the serious category, the implementation of leadership values ​​(maqṣudal-Istikhlāf) through the judge's discretion by prioritizing mediation as a solution for resolving divorce cases